Anti-influenza Virus Activity of Methylthio-Formycin Distinct From That of T-705 - Takizawa, Naoki; Takada, Hisashi; Umekita, Maya; Igarashi, Masayuki; Takahashi, Yoshiaki (Frontiers in Microbiology, 2022)
Seasonal influenza virus epidemics result in severe illness, and occasionally influenza pandemics cause significant morbidity and mortality, although vaccines and anti-influenza virus drugs are available. By screening an in-house library, we identified methylthio-formycin (SMeFM), an adenosine analog, as a potent inhibitor of influenza virus propagation. SMeFM inhibited the propagation of influenza A and B viruses (IC50: 34.1 nM and 37.9 nM, respectively) and baloxavir and neuraminidase inhibitor low-sensitive strains, but not T-705 (Favipiravir) low-sensitivity strain. However, the association of T-705 and SMeFM inhibited the propagation of the influenza virus not in an antagonistic but in a slightly synergistic manner, suggesting that SMeFM has targets distinct from that of T-705. SMeFM induced A-to-C transversion mutations in virus genome RNA, and SMeFM triphosphate did not inhibit in vitro viral RNA synthesis. Our results show that SMeFM inhibits the propagation of the influenza virus by a mechanism different from that of T-705 and is a candidate for treating influenza virus infections.